2020
DOI: 10.1101/2020.08.31.275164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate change alters plant-herbivore interactions

Abstract: Plant-herbivore interactions have evolved in response to co-evolutionary dynamics, along with selection driven by abiotic conditions. We examine how abiotic factors influence trait expression in both plants and herbivores to evaluate how climate change will alter this long-standing interaction. The paleontological record documents increased herbivory during periods of global warming in the deep past. In phylogenetically-corrected meta-analyses, we find that elevated temperatures, CO2 concentration, drought str… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 162 publications
0
4
0
1
Order By: Relevance
“…Environmental factors affect the growth, development and distribution of plants (Hamann et al, 2021;Li and Zhang, 2021). Climate is one of the key factors shaping the future distribution of plants (Gomes et al, 2020;Tang et al, 2021).…”
Section: Key Bioclimatic Factors Influencing Suitable Habitats Of Hol...mentioning
confidence: 99%
“…Environmental factors affect the growth, development and distribution of plants (Hamann et al, 2021;Li and Zhang, 2021). Climate is one of the key factors shaping the future distribution of plants (Gomes et al, 2020;Tang et al, 2021).…”
Section: Key Bioclimatic Factors Influencing Suitable Habitats Of Hol...mentioning
confidence: 99%
“…However, recent reviews on combined stress have also indicated that elevated drought, high temperature, and nutrient conditions make plants more vulnerable to pest or pathogen infection (Cohen and Leach, 2020;Desaint et al, 2021;Hamann et al, 2020;Savary and Willocquet, 2020).…”
Section: Effects Of Combined Stress On Yield and Yield-attributing Tr...mentioning
confidence: 99%
“…Herbivory plays a central role in the ecology and evolution of tropical forest tree species, shaping their physiology and distribution (Coley and Barone, 1996;Fine et al, 2004;Kursar et al, 2009;Muehleisen et al, 2020), forest community composition (Fine et al, 2004;Kursar et al, 2009;Muehleisen et al, 2020) and other ecosystem processes, such as nutrient cycling (Metcalfe et al, 2014). Furthermore, projected shifts in rainfall and temperature with global climate change may influence plant-insect interactions, including herbivory (Hamann et al, 2021). Thus, understanding factors that influence herbivory rates in tropical forests is pivotal.…”
Section: Introductionmentioning
confidence: 99%